Simultaneuos observation of traveling ionospheric disturbances in the northern Hemispheres - Valladares, Cesar Enrique (2009)
Measurements of total electron content (TEC) using 263 GPS receivers located in the North and South America continents are presented to demonstrate the simultaneous existence of traveling ionospheric disturbances (TID) at high, mid, and low latitudes, and in both Northern and Southern Hemispheres. The TID observations pertain to the magnetically disturbed period of 29–30 October 2003 also known as the Halloween storm. The excellent quality of the TEC measurements makes it possible to calculate and remove the diurnal variability of TEC and then estimate the amplitude, wavelength, spectral characteristics of the perturbations, and the approximate velocity of the AGW. On 29 October 2003 between 17:00 and 19:00 UT, there existed a sequence of TEC perturbations (TECP), which were associated with the transit of atmospheric gravity waves (AGW) propagating from both auroral regions toward the geographic equator. A marked difference was found between the northern and southern perturbations. In the Northern Hemisphere, the preferred horizontal wavelength varies between 1500 and 1800 km; the propagation velocity is near 700 m/s and the perturbation amplitude about 1 TEC unit (TECu). South of the geographic equator the wavelength of the TECP is as large as 2700 km, the velocity is about 550 m/s, and the TECP amplitude is 3 TECu. Concurrently with our observations, the Jicamarca digisonde observed virtual height traces that exhibited typical features that are associated with TIDs. Here, it is suggested that differences in the local conductivity between northern and southern auroral ovals create a different Joule heating energy term. The quality of these observations illustrates the merits of GPS receivers to probe the ionosphere and thermosphere